Optimization of nutraceuticals extraction - Anwar, Farooq; Malik, Shanza; Jabeen, Ayesha; Ayub, Muhammad Adnan; Zafar, Muhammad Nadeem; Zubair, Muhammad (Springer US, 2024)
Optimization is the selection of the most efficient system that can resolve and help in attaining the objective functions by designing or operating various optimized procedures. In this chapter, optimized extraction of nutraceuticals is discussed. With an increasing demand for nutraceuticals, there is now greater focus on nutrapharmaceutical industry that produces safer natural products/extracts in a sustainable manner by costeffective and eco-friendly green extraction routes. So the strategies that need to be devised for this purpose include the evaluation and optimization of various extraction variables (particle size, material/solvent ratio, extraction time and cycle, type of extraction technique, extraction conditions like temperature, agitation rate, etc.) that aim to control the stability of the bioactives and achieve the sustainable quality of the end-use nutraceutical products. In this chapter, we have focused on the optimized extraction of nutraceuticals along with the recent technological trends that are applicable toward the recovering of best possible levels of such high-value components.